The Impact of Bartonella VirB/VirD4 Type IV Secretion System Effectors on Eukaryotic Host Cells - Fromm, Katja; Dehio, Christoph (Frontiers in Microbiology, 2021)
Bartonella spp. are facultative intracellular pathogens that infect a wide range of mammalian hosts including humans. The VirB/VirD4 type IV secretion system (T4SS) is a key virulence factor utilized to translocate Bartonella effector proteins (Beps) into host cells in order to subvert their functions. Crucial for effector translocation is the C-terminal Bep intracellular delivery (BID) domain that together with a positively charged tail sequence forms a bi-partite translocation signal. Multiple BID domains also evolved secondary effector functions within host cells. The majority of Beps possess an N-terminal FIC (filamentation induced by cAMP) domain and a central connecting oligonucleotide binding (OB) fold. FIC domains typically mediate AMPylation or related posttranslational modifications of target proteins. Some Beps harbor other functional modules, such as tandem-repeated tyrosine-phosphorylation (EPIYA-related) motifs. Within host cells the EPIYA-related motifs are phosphorylated, which facilitates the interaction with host signaling proteins. In this review, we will summarize our current knowledge on the molecular functions of the different domains present in Beps and highlight examples of Bep-dependent host cell modulation.